230k views
3 votes
If f(x) = 2x - 6 and g(x) = x, what is (g°7 (6)?

User Joche Wis
by
5.3k points

2 Answers

4 votes

Answer: B. -112 on edge :)

User Gvs Akhil
by
5.3k points
5 votes

Answer:

g(f(6)) = 6

Explanation:

The two functions are:

f(x) = 2x - 6

g(x) = x


$ f \circ g(x) = f(g(x)) $

i.e., g(x) becomes the input for f(x).

Here, we are asked to determine g(f(x)).

We will have: g(f(x)) = g(2x - 6)

Since, g(x) = x, g(2x - 6) = 2x - 6

When x = 6, g(f(6)) = 2(6) - 6

= 12 - 6 = 6

g(f(6)) = 6 is the answer.

User Emely
by
5.0k points